The economic policies of the next US president - Barry Eichengreen (EconPol Forum, 2024)
The next president of the United States will have to address the country's chronic budget deficits and spiraling debt. Unfortunately, neither candidate has a coherent plan. Neither candidate is committed to free trade. Whereas Trump's trade policies will be conditioned by animosity toward China, Harris's will be shaped by climate and labor standards. A dramatic difference between the two candidates is on climate policy, where Trump proposes to again withdraw the US from the Paris Agreement and to expand the use of oil and gas, whereas Harris was a proponent of the 2019 New Green Deal. Trump promises to reduce the cost of living by elimi nating red tape and restrictions on oil and gas exploration and extraction, while Harris has promised to eliminate price gouging and other anti-competitive practices and to provide subsidies for affordable housing.
Keywords: 330